EU labour market behaviour during the 'Great Recession' - Arpaia, Alfonso; Curci, Nicola (Brussels, 2010)
"This paper provides an analysis of the labour market adjustment to the 2008-2009 recession. It highlights differences in the response of employment and unemployment across countries and different socioeconomic groups. For all EU Member States, it provides evidence of the developments during the crisis of the monthly job finding and separation rates. This helps to assess whether the increase in unemployment is due to an increase of job separation or to a decline in the job finding rate. The paper discusses the risks of jobless growth and compares the dynamics of unemployment and employment across different periods. It provides evidence of an asymmetric response over the cycle, with recessions being characterised by more job destruction than by job creation in the following recoveries. The analysis of the wage dynamics suggests that there has been an adjustment in the compensation per employee led by the variable component; yet, this has not been sufficient to avoid the increase in the nominal unit labour costs due to labour hoarding."